Intelligent agent-based simulation for supporting operational planning in country reconstruction. (1st January 2013) - Bruzzone, Agostino G.
This paper proposes the development of conceptual models for supporting operational planning in complex scenarios characterised by critical issues such as natural disasters, crisis, asymmetric warfare, etc. In this context, it is fundamental to take into consideration social and psychological aspects; so the author developed a special kind of intelligent agents (IAs) driving computer generated forces (CGF), specific for normalisation and stabilisation phase with particular focus on CIMIC and PSYOPs operations, in order to consider the human aspects as well as the impact of social networks on this context as further development of their IA-CGF. The research provides an overview about conceptual models to be implemented in a simulator for supporting CIMIC and PSYOPs operations planning during stabilisation and normalisation phases in country reconstruction. The author proposes the general architecture of the simulator, focusing on objects attributes and features and verification, validation and accreditation (VV&A) process.